E-230 Comparison of PED and FRED flow diverters for posterior circulation aneurysms: a propensity-score matched cohort study. (4th August 2020) - Griessenauer, C; Enriquez-Marulanda, A; Xiang, S; Hong, T; Zhang, H; Taussky, P; Grandhi, R; Waqas, M; Tutino, V; Siddiqui, A; Levy, E; Ogilvy, C; et al.
Abstract : Introduction/Purpose: Flow diversion is a popular endovascular treatment for cerebral aneurysms, but studies comparing different types of flow diverters are scarce. Here, we performed a propensity score-matched cohort study comparing the Pipeline Embolization Device (PED) and Flow Redirection Intraluminal Device (FRED) for posterior circulation aneurysms. Materials and Methods: Consecutive aneurysms of the posterior circulation treated at 25 neurovascular centers with either PED or FRED were collected. Propensity score matching was used to control for age, duration of follow-up imaging, adjunctive coiling, and aneurysm location, size, and morphology; previously ruptured aneurysms were excluded. The two devices were compared for the following outcomes: procedural complications, aneurysm occlusion, and functional outcome. Results: A total of 375 aneurysms of the posterior circulation were treated in 369 patients. The PED was used in 285 (77.2%) and FRED in 84 (22.8%) of procedures. Aneurysms treated with the PED were more commonly fusiform in morphology and larger in size compared to the FRED aneurysms. To account for these important differences, propensity score matching was performed resulting in 44 PED and FRED unruptured aneurysm pairs. There were no differences between the two devices in terms of occlusion status, functional outcome, and neurologic complications. Conclusion: Comparative analysis of PED and FRED for the treatment of unruptured posterior circulation aneurysms did not identify significant differences in aneurysm occlusion status at last follow-up, functional outcome, or neurologic complications. Disclosures: C. Griessenauer: None. A. Enriquez-Marulanda: None. S. Xiang: None. T. Hong: None. H. Zhang: None. P. Taussky: None. R. Grandhi: None. M. Waqas: None. V. Tutino: None. A. Siddiqui: None. E. Levy: None. C. Ogilvy: None. A. Thomas: None. C. Ulfert: None. M. Möhlenbruch: None. L. Renieri: None. N. Limbucci: None. C. Parra-Fariñas: None. J. Burkhardt: None. P. Kan: None. L. Rinaldo: None. G. Lanzino: None. W. Brinjikji: None. E. Müller-Thies-Broussalis: None. M. Killer-Oberpfalzer: None. C. Islak: None. N. Kocer: None. M. Sonnberger: None. T. Engelhorn: None. M. Ghuman: None. V. Yang: None. A. Salehani: None. M. Harrigan: None. I. Radovanovic: None. A. Dmytriw: None.